Mengubah Perilaku Menyimpang: Keberhasilan Program Sosialisasi Kenakalan Remaja di Tingkat SMA - Stepi Aodia Jesika; Selviae; Siska; Noverinda Maharani; Adinda Nur Ramadan; Reni Agustiani (NAJWA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program is motivated by the high rate of juvenile delinquency among high school students, particularly at SMAN 1 Paku Barito Timur, which includes truancy, smoking, alcohol consumption, and illegal racing. The purpose of this program is to enhance students' understanding of the definition, types, causal factors, impacts, and countermeasures of juvenile delinquency. The method used in this community service is socialization and mentoring with a participatory approach, implemented through three main stages: initial observation, the implementation of socialization using interactive lectures, group discussions, and question-and-answer sessions, as well as evaluation of students' understanding through pre-test and post-test questionnaires. The results showed a significant improvement in students' understanding across all materials. On the definition of juvenile delinquency, students' understanding increased from 80% to 100%; on the types of juvenile delinquency, it increased from 90% to 100%; on internal and external factors, it increased from 0% to 100%; on the impacts of juvenile delinquency, it increased from 10% to 100%; and on strategies to overcome juvenile delinquency, it increased from 0% to 100%. The implication of this program is that interactive and participatory socialization is effective in increasing students' awareness of the dangers of juvenile delinquency, so it needs to be continued with ongoing mentoring programs and collaboration between schools, parents, and the community.